1998
DOI: 10.1116/1.589811
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron imaging as a two-dimensional dopant profiling technique: Review and update

Abstract: Articles you may be interested inHigh resolution quantitative two-dimensional dopant mapping using energy-filtered secondary electron imaging Secondary electron ͑SE͒ imaging of semiconductors reveals contrast between n-and p-type areas that can serve as the basis for a two-dimensional dopant profiling technique. In this article, recent experiments that address sensitivity, spatial resolution, calibration methodology, p/n junction effects, and sample preparation issues are reviewed and discussed for boron doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 4 publications
(3 reference statements)
6
57
1
Order By: Relevance
“…In addition, the height of the Schottky barrier will be a function of the dopant concentration; thus, the SE yield will vary accordingly. This is as observed by Venables et al 8 …”
Section: Metal-semiconductor Contactsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, the height of the Schottky barrier will be a function of the dopant concentration; thus, the SE yield will vary accordingly. This is as observed by Venables et al 8 …”
Section: Metal-semiconductor Contactsupporting
confidence: 83%
“…If a region within this substrate is doped to produce features of p-type material, then it is possible to obtain, in the LVSEM mode, different SE brightness levels from these two regions giving a distinct contrast between them. Venables et al,8 in an attempt to quantify the SE contrast profiles, found a linear relationship between the observed SE intensity and the logarithm of the dopant concentration of boron-doped silicon in the range 4 ð 10 16 cm 3 to 3 ð 10 20 cm 3 , as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 87%
“…A resolution up to 1 nm is achievable (Elliott et al, 2002), and sensitivity to dopant concentrations ranging from 10 14 up to 10 20 dopants cm -3 can be obtained at a quantification accuracy of at least ± 3 % (Perovic et al, 1998;Venables et al, 1998;Elliott et al, 2002, Chee, 2009. As SE doping contrast is able to characterise dopants with high sensitivity over the required range and resolution, it is highly viable compared to a number of alternative techniques of limited range and resolution, are time-consuming, costly or destructive, or provide only 1-D measurements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a built-in potential such that the energy bands in the p-type region are shifted up relative to those in the n-type region, thus reducing E b , the energy required to escape to the detector. This effect has been used mainly to image doped regions in semiconductors [4][5][6][7][8][9] and the technique is often called "doping contrast". In addition, the electrostatic potential distribution of a cross-section of a p-n junction has been mapped by subtracting two images obtained at different bias voltages [10].…”
mentioning
confidence: 99%